Aktivitas Antibakteri Dari Bakteri Probiotik Dalam Melawan Propionibacterium acnes Dan Staphylococcus epidermidis - Adhitya Naufal Pribadhi; Sri Mastuti; Ellyka Purwaningrum (Indobiosains, 2023)
Introduction; Acne vulgaris or commonly called acne, is a disease that is generally suffered by teenagers. Acne is caused by the formation of colonies of pathogenic bacteria such as Propionibacterium acnes and S. epidermidis. Excessive use of antibiotics can lead to bacterial resistance. Therefore, there is a need for other alternatives to the use of antibiotics. Probiotics can be an alternative as an antimicrobial against P. acnes and S. epidermidis bacteria. The aim of this study was to determine the antibacterial activity of probiotic bacteria, namely W. confusa against P. acnes and S. epidermidis. Method; antimicrobial test by agar diffusion method. The positive control used tetracycline antibiotics and the negative control used a blank disk. Results; the presence of antimicrobial activity against P. acnes and S. epidermidis, indicated by the average zone of inhibition in P. acnes of 13.4 mm and S. epidermidis 14 mm. Conclusion; Probiotic bacteria are able to inhibit the growth of pathogenic bacteria that cause acne, namely P. acnes and S. epidermidis.Keywords: Acnes vulgaris, Probiotics, P. acnes, S. epidermidis